Surface ripple and erosion rate of stainless steel under elevated temperature erosion by angular solid particles. (February 2014) - Wang, Shun-sen; Cai, Liu-xi; Mao, Jing-ru; Liu, Guan-wei; Di, Juan
The actual industrial erosion caused by the impingement of particles swarming from different perspectives is often different from the single-angle impingement of solid particle in the erosion test. In order to predict the erosion problems in practical engineering more reasonably, a series of elevated temperature erosion tests were conducted to study the surface ripple and enduring erosion behavior of heat-resistance stainless steel suffering from the single-angle impingement or multiangle alternative impingement of angular particles. The test results indicated that the surface of target materials with good ductility produced large-scaled transverse ripples and small-scaled longitudinal ripples after experienced a long-time single-angle impingement of angular solid particles under a 773–873-K high-temperature environment. The longitudinal ripples could accelerate the emergence and development of large-scaled transverse ripples. Initial erosion scars caused the differentiation of material deformability and plastic flow in the different locations of concave–convex scars, which further drove the evolution of the surface morphology from disordered scars to coherent ripples under the sustained attack of high-velocity particles. The more dimples the eroded surface of target material produced, it was easier for the target materials to produce coherent ripple. However, the interactions among the erosion behaviors with different attack angles made initial concave–convex scars difficult to evolve to coherent ripples under the multiangle alternative erosion. Further statistical results of erosion tests indicated that it can basically satisfy the practical engineering need by taking the erosion rate of initial surface layer as the erosion rate of the target material within the whole life cycle.